Assessment of the Physical Environment of Child Care Institutions - Hrishikesh Purandare*; Ashwini Pethe (International Journal of Architectural Design and Planning, 2023)
The environment in which orphans live is considered a vulnerability by several international organizations that refer to parentless children as “at risk.” A child care facility accommodates these distressed children who lack parental care, by providing a safe protective environment that contributes to the well-being of the child as well as providing a nurturing environment for their development. All resident children within institutional care have to share not only the care and love given by the care givers but also have to negotiate the use of facilities, regardless of the age, gender abilities, and needs of the child. Thus, the children who are cohabiting these negotiated spaces tend to find comfort in their physical surroundings. Studies pertaining to the psycho-social well-being of the child have been carried out for decades; however, little is known about the quality of the physical environment in these establishments. Using the children’s physical environment rating scale, this article measures the quality of physical environment in five child care institutions located in Pune, India. Analysis of the collected data provides an understanding as to whether the physical environment provides opportunities for child development.
Keywords: Physical environment quality; child care institutions; child well-being; facilities; spatial design